3, 3′, 4, 4′, 5-Pentachlorobiphenyl Inhibits Drug Efflux Through P-Glycoprotein in KB-3 Cells Expressing Mutant Human P-Glycoprotein. Issue 3 (29th July 2004) - Fujise, Hiroshi; Sasawatari, Shigemi; Annoura, Takeshi; Ikeda, Teruo; Ueda, Kazumitsu
Abstract : The effects on the drug efflux of3, 3 ′, 4, 4 ′, 5 -pentachlorobiphenyl (PCB-126), the most toxic of all coplanar polychlorinated biphenyls (Co-PCBs), were examined in KB-3 cells expressing human wild-type and mutant P-glycoprotein in which the 61st amino acid was substituted for serine or phenylalanine (KB3-Phe 61 ). In the cells expressing P-glycoproteins, accumulations of vinblastine and colchicine decreased form 85% to 92% and from 62% to 91%, respectively, and the drug tolerances for these chemicals were increased. InKB3-Phe 61, the decreases in drug accumulation were inhibited by adding PCB-126 in a way similar to that with cyclosporine A: by adding 1μ M PCB-126, the accumulations of vinblastine and colchicine increased up to 3.3- and 2.3-fold, respectively. It is suggested that PCB-126 decreased the drug efflux by inhibiting the P-glycoprotein inKB3-Phe 61 . Since there were various P-glycoproteins and many congeners of Co-PCBs, this inhibition has to be considered a new cause of the toxic effects of Co-PCBs.